Body Mass Index and Waist Circumference Associations with Blood Pressure: Hubungan Indeks Massa Tubuh dan Lingkar Pinggang dengan Tekanan Darah - Bea Uljannatun Putri Fisis Paramanandi; Sri Lestari Utami; Jimmy Hadi Widjaja; Febtarini Rahmawati (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Body mass index and waist circumference are widely used anthropometric indicators to describe nutritional status and body fat distribution related to cardiovascular risk, including blood pressure changes in young adults. Specific Background: Medical students, particularly those in early academic years, are generally perceived as healthy but may experience overweight or obesity during their study period, which warrants early observation of blood pressure patterns. Knowledge Gap: Empirical evidence focusing on the relationship between body mass index, waist circumference, and systolic and diastolic blood pressure among early-year medical students remains limited and inconsistent. Aims: This study aimed to examine the relationship between body mass index and waist circumference with systolic and diastolic blood pressure among medical students of Wijaya Kusuma University Surabaya, class of 2024. Results: Based on an observational cross-sectional design involving 95 students, Pearson correlation analysis demonstrated no significant relationship between body mass index or waist circumference and systolic or diastolic blood pressure (p > 0.05). However, chi-square analysis identified a significant association between body mass index and systolic blood pressure, as well as between waist circumference and systolic blood pressure. Novelty: This study provides specific evidence from an early-year medical student population showing that anthropometric indicators are not consistently associated with blood pressure despite a substantial proportion of overweight and obesity. Implications: The findings emphasize the importance of early anthropometric screening and preventive strategies in medical students to address potential cardiovascular risk factors before clinical manifestations emerge. Highlights • Anthropometric indicators showed no consistent correlation with systolic and diastolic blood pressure• Overweight and obesity were prevalent among early-year medical students• Significant associations appeared only in categorical systolic blood pressure analysis Keywords Body Mass Index; Waist Circumference; Blood Pressure; Medical Students; Anthropometric Indicators